Mathematical Modeling to Measure the Level of Terrorism Deradicalization Effectiveness - Anatansyah Ayomi Anandari (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2022)
The general aim of deradicalization is to make terrorists or groups of perpetrators of violence willing to leave or break away from acts and activities of terrorism. The method in this study is quantitative-descriptive which will provide mathematical modelling to calculate the number of terrorist prisoners in Indonesia that have been successfully handled by the National Counter-Terrorism Agency (Badan Nasional Penanggulangan Terorisme) through a deradicalization program. The purpose of this study is to determine the effectiveness of the deradicalization program of the National Counter-Terrorism Agency in reducing the number of terrorist prisoners in Indonesia. The deradicalization program carried out by the government through the National Counter-Terrorism Agency aims to neutralize the ideological foundations of both militant and radical groups. The deradicalization used by the BNPT is the formula currently being implemented to deal with the threat of terrorism and also those related to radical groups. The mathematical model for terrorist deradicalization efforts by the National Counter-Terrorism Agency is (dN(t))/dt=T-E-kN(t)-pN(t)-lN(t) .